Using the Body to Retrieve the Soul: Learning From Modern Chinese Shaman Phenomenology of the Body - Feng, Kan (Review of religious research, 2023)
This commentary attends to religion and the body as a philosophical approach to decentering Western and Christian traditions in understanding of spiritual healing. Prior soul-centered shamanic soul retrieval theories cannot explain the beliefs and practices of modern Chinese shamans. This commentary draws upon phenomenology of the body to assert that soul retrieval of Chinese shamans is not a purely spiritual mystical event or a purely material event. Rather, it is both. Shamans utilize a body technique to adjust, configure, and reposition the dislocated state of the patient’s body by temporarily sharing a body (einleibung) with the patient. Providing this context can foster new approaches to understanding religious and spiritual healing.